Biomonitoring of polycyclic aromatic hydrocarbons in firefighters at fire training facilities and in employees at respiratory protection and hose workshops - Koslitz, Stephan; Heinrich, Birgit; Käfferlein, Heiko U.; Koch, Holger M.; Pelzl, Tim; Pitzke, Katrin; Köster, Daniel; Weiß, Tobias; Harth, Volker; Brüning, Thomas; Behrens, Thomas; Taeger, Dirk (Frontiers in Public Health, 2023)
Polycyclic aromatic hydrocarbons (PAH) are carcinogenic to humans and are formed by incomplete combustion. PAH are always present during firefighting operations and fire department members can be exposed at the workplace. Here, we analysed 1-hydroxypyrene (1-OHP) in 36 urine samples of nine firefighters before and after fire-training sessions and 32 urine samples of eight employees in respiratory protection and hose workshops. To assess PAH breakthroughs the personal protective equipment and potential dermal uptake, some of the workshop employees wore cotton garments under their regular workwear. Then, cotton samples were examined for 17 semi-and low-volatile PAH. After firefighting exercises, we observed about a fivefold increase in mean 1-OHP concentrations from 0.24 µg/L to 1.17 µg/L (maximum: 5.31 µg/L). In contrast, 1-OHP levels in workshop employees were found to be low with the majority of urine samples yielding concentrations below the limit of quantification (LOQ 0.05 µg/L, maximum: 0.11 µg/L). Similarly, low PAH levels were found on the workshop employees' underline cotton garments with maximum concentrations of 250 and 205 ng/g for pyrene and benzo[a]pyrene. In conclusion, significant increases of 1-OHP in urine was observed in firefighters after training sessions, whereas work-related exposures remained low in workshop employees.